Chichibabin "isodesmopyridine" synthesis. Issue 13 (28th March 2019) - Fuse, Wakana; Imura, Akiho; Tanaka, Nao; Usuki, Toyonobu
Graphical abstract: Highlights: First total synthesis of isodesmopyridine was achieved. The biomimetic synthesis involved Chichibabin pyridine synthesis. The synthesis was accomplished from allysine and ammonium acetate. Abstract: 2, 3, 5-Trisubstituted pyridine isodesmopyridine is one of the elastin crosslinking amino acid which was isolated from the acid hydrolysates of bovine ligamentum nuchae. Biosynthesis of isodesmopyridine is believed to undergo via Chichibabin pyridine synthesis starting from aldehydes and an ammonia. Herein, we report the first total synthesis of isodesmopyridine through Chichibabin pyridine synthesis from allysines with protecting groups and ammonium salts in the presence of 50 mol% Pr(OTf)3 with the optimization of the reaction conditions.